Hakekat Peraturan Pemerintah Pengganti Undang-Undang (PERPPU) Dalam Peraturan Perundang-Undangan di Negara Republik Indonesia - Asti Dwiyanti (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study is intended to investigate the size or reason for the issuance of a PERPPU by the President, as well as the nature or content of a state crisis that creates a convincing state of emergency. This research uses the Literature Review Comparative Study procedure, using secondary information. In granting the PERPPU, the President's power appears to be